Pengukuran Kinerja Supply Chain pada Konstruksi Gedung Bertingkat dengan Menggunakan Pendekatan Metode SCOR (Supply Chain Operations Reference) - Fitrianto, Taufiq; Wibowo, Mochamad Agung; Hatmoko, Jati Utomo Dwi (Department of Civil Engineering, Diponegoro University, 2020)
Construction industry has a vital role in Indonesia’s economic growth. Infrastructure projects have been the priorities in the past five years consistent with RPJMN (National Medium Term Development Plan). It’s evident in the percentage of contribution of the construction industry, i.e. 10.2%, to Gross Domestic Product (PDB) and 6.34 million employments (5.3% national labors). However, it isn’t followed by efficiency of the construction industry. Increased cost, implementation, delay, conflict and dispute are some problems which arise from fragmentation and causes the construction industry to be known as an inefficient industry. A possible approach to solve fragment problem is studying the supply chain of the construction industry. The present study aimed to measure supply chain performance of construction using SCOR (supply chain) method, the impact and mitigation. The result was that the handling performed in TSM Bali project resulted in 5.56% of indirect waste, 8.63% of direct waste, and 443,711 tonCO2 of carbon footprint